Asthma Management at Discharge from the Emergency Department: A Descriptive Study - Pascale Gervais; Isabelle Larouche; Lucie Blais; Anne Fillion; Marie-France Beauchesne (Canadian Respiratory Journal)
BACKGROUND: The management of asthma remains suboptimal despite the publication of Canadian asthma guidelines in 1999.